Effects of Alchemilla mollis and Alchemilla persica on the wound healing process (Bangladesh Journal of Pharmacology, 2016)
Alchemilla mollis, is used in traditional medicine for the treatment of wounds and excessive menstruation. Aqueous methanol extracts of A. mollis and A. persica were evaluated for wound healing acivity by using linear incision and circular excision wound models along with hydroxyproline estimation and histopathological analysis. Anti-inflammatory effect was determined according to Whittle method. The extracts prepared from the aerial parts of A. mollis and A. persica exerted significant wound healing activity with the tensile strength values of 39.3% and 33.3%, respectively, and with the contraction values of 51.4% and 43.5%, respectively. Hydroxyproline estimation and histopathological analysis also confirmed the results. The extracts of A. mollis and A. persica showed significant anti-inflammatory activity with the values of 30.6% and 26.6% respectively. These results showed that A. mollis and A. persica possess significant wound healing and anti-inflammatory activities.Video Clip of Methodology:Circular excision wound model: 2 min   Click to watch